PERANCANGAN SISTEM INFORMASI AKADEMIK BERBASIS WEB PADA PROGRAM DIPLOMA III MANAJEMEN INFORMATIKA UM METRO LAMPUNG - M.M, Sudarmaji (Jurnal Informatika, 2012)
Academic Information Systems on the Web-Based Information Management D3 Studies Program, University of Muhammadiyah Metro Lampung, is a system that provides information activity reports online activity in the form of student grade reports, attendance reports, reports of lectures, and other information related to the academic field. Academic Information System web-based, so it helps the speed and quality in the delivery of information. In addition to the web-based data information can be accessed at a time and place not specified. In this system, the menu can only be accessed by certain users such as students, faculty, and administrators. Academic information system development is expected to provide the perfect solution for students and faculty. Where this system is used in building tools and development systems are Data Flowchart and using PHP and HTML programming language and MySQL as the databaseKeywords: Information Systems, programming language, and database